Salvage Therapy after Allogeneic Hematopoietic Cell Transplantation: Targeted and Low-Intensity Treatment Options in Myelodysplastic Syndrome and Acute Myeloid Leukemia - Katie Culos; Michael Byrne (Clinical Hematology International, 2019)
Patients with high-risk myeloid neoplasms, including myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML), are offered allogeneic hematopoietic cell transplantation (alloHCT) to improve the likelihood of long-term disease control. More than 50% of patients with high-risk disease will relapse after HCT and face a poor prognosis with shortened survival. The recent development of targeted therapies and effective, low-intensity treatment strategies will likely improve the outcomes of these patients. In MDS, hypomethylating agents (HMAs) are the mainstay of salvage therapy but new treatments with APR-246 and luspatercept demonstrate excellent results in phase 1 and phase 3 clinical studies, respectively. In AML, new directed agents in the relapsed/refractory setting include gilteritinib (FLT3-ITD/-TKD), ivosidenib (IDH1), and enasidenib (IDH2). In patients without targetable mutations, HMAs may be used, and early data with venetoclax-based regimens are encouraging.